Improving Students’ Reading Ability Through Collaborative Strategic Reading at Eight Grade SMP Nasional Karimbow - Wua, Nafva; Muntuuntu, Meity; Rombepajung, Paula A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
On the other hand, reading proficiency for SMP Nasional Karimbow students remains low. Students have certain challenges when it comes to developing their reading comprehension, particularly when it comes to understanding narrative texts. Students find it tedious to work with narrative texts because they find it hard to understand the content and come to their own conclusions about it. This study was carried out at SMP Nasional Karimbow, which is situated in North Sulawesi's East Motoling, South Minahasa District. The research was carried out in Mei 2023. The eighth grade students of SMP Nasional Karimbow participated in this study during the academic year 2022–2023. The researcher produced study instruments in the form of pre- test and post- test to tests students’ abilities before and after carrying out the treatment. The researcher employed testing in this study. Students take two different types of tests: a pre-test prior to CSR and a post-test following CSR. Studies conducted in the tenth grade at SMA Swadhama Werdhi Agung in 2022–2023 suggest that CSR could enhance reading comprehension. 46.25 was the pre-test score (X), and 81.42 was the post-test score (X). In the SMP Nasional Karimbow narrative text on reading comprehension, collaborative strategic reading is beneficial